2016
DOI: 10.1001/jamaoto.2016.0194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Documentation Improvement Program for an Academic Otolaryngology Practice

Abstract: After educational sessions, multiple measures of patient acuity increased significantly owing to improved documentation of common comorbid conditions. Although physicians intuitively appreciate the importance of good documentation, education on the technical aspects of coding can significantly improve the quality and accuracy of clinical records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 9 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Documentation of TB symptom screening before ART was often missing with only 36% of medical records documenting screening for at least one TB symptom and only 11% of records documenting screening for all five symptoms recommended by national guidelines. Even though it is possible that some patients were screened for TB symptoms but screening was not documented, this still represents incomplete adherence to national TB screening policy, which requires both TB screening implementation and documentation [ 19 , 20 ]. Low rates of documented TB screening at ART facilities have been reported from other countries, including Mozambique, where only 61% of patients were documented to have been screened for TB before ART and only 5% were documented to have been screened for all five MOH-recommended TB symptoms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of TB symptom screening before ART was often missing with only 36% of medical records documenting screening for at least one TB symptom and only 11% of records documenting screening for all five symptoms recommended by national guidelines. Even though it is possible that some patients were screened for TB symptoms but screening was not documented, this still represents incomplete adherence to national TB screening policy, which requires both TB screening implementation and documentation [ 19 , 20 ]. Low rates of documented TB screening at ART facilities have been reported from other countries, including Mozambique, where only 61% of patients were documented to have been screened for TB before ART and only 5% were documented to have been screened for all five MOH-recommended TB symptoms [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several published papers have sought to improve documentation through tool kits, didactics, and personal feedback. 1,35,814 Economic journals have also focused on medical documentation. 2 Several studies have reported that educational sessions improve technical aspects of coding.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several studies have reported that educational sessions improve technical aspects of coding. 1,8 Another publication demonstrated that personal feedback could improve aspects of resident learning. 9 One curriculum utilized volunteer accrual and self-learning with self-evaluation as a means of education.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous efforts aiming to improve the quality of nursing documentation have been undertaken. Evidence-based approaches to improving documentation include interventions such as national clinical audits with data feedback [21,22], the availability of documentation policies and guidelines [10], information sharing [23], provision of training [24][25][26], strengthening nursing hospital leadership, engaging key staff into improvement processes [9], and the use of a framework for recording nursing daily free-text notes [26,27]. Nursing documentation can also be improved by indirect workforce and structural interventions, such as increased nurse to patient ratios and addressing equipment shortages, as these interventions make it easier for nurses to complete documentation [22].…”
Section: Introductionmentioning
confidence: 99%